Performance trends in individual medley events during FINA World Master Championships from 1986 to 2014 - Nikolaidis, P. T.; Knechtle, B. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Performance trends during the last decades in elite individual medley swimmers are known, but not for age groups swimmers. Therefore, the aim of the present study was to examine participation and performance trends in age groups swimmers competing in FINA World Masters Championships (1986-2014) in individual 200-m and 400-m medley. METHODS: We included all swimmers (6424 women, 7588 men) for each distance and age groups (25-29 to 95-99 years) in the analysis to avoid a selection bias by limiting to a fixed sample (e.g. the ten fastest). Changes in participation and changes in sex difference across editions were analyzed using linear regression models. Changes in performance across editions were analyzed using a mixed-effects regression model with finisher as random variable to consider finishers who completed several races. Sex, distance and calendar year were included as fixed variables. We also considered interaction effects between sex and distance. The men-to-women ratio was compared using a paired t-test. RESULTS: In 200 m, the participation of women increased from 35-39 to 75-79 years and of men from 35-39 to 85-89 years (P<0.05). In 400 m, the participation of women increased from 50-54 to 75-79 years and of men from 60-64 to 85-89 years (P<0.05). From 25-29 to 90-94 years, women and men improved performance in both editions (P<0.05). Men were faster than women from 25-29 to 80-84 years (P<0.05), but not in 85-90 and 90-94 years. Sex and distance showed a significant interaction from 25-29 to 85-89 years (P<0.05), but not in 90-94 years. Women reduced the gap to men in 40-44 and 45-49 years in 200 m, and 40-44 years in 400 m (P<0.05). CONCLUSIONS: In summary, the participation increased in older age groups (>35 years), women and men from 25-29 to 90-94 years improved, and men were faster than women from 25-29 to 80-84 years, but not from 85-89 to 90-94 years. These data suggest that master swimmers will continue to increase participation and improve performance in individual medley. The findings of the present study might help coaches and fitness trainers of medley swimmers to tailor their training programs considering the age of their swimmers.